Risk factors for lateral pelvic lymph node metastasis in patients with rectal neuroendocrine tumors: a systematic review and meta-analysis - Chen, Ziyue; Zhu, Dajian (Frontiers in Oncology, 2025)
Background and objectiveLateral pelvic lymph node (LPLN) metastasis is one of the prominent reasons for local recurrence in patients with rectal neuroendocrine tumors (RNETs). The evaluation criteria of lateral lymph node metastasis for patients and the indications and value of lateral pelvic lymph node dissection (LPLD) have been controversial. Total mesorectal excision (TME), a conventional surgical treatment for RNETs, excluding lateral lymph nodes, may be one of the reasons for postoperative local recurrence. This study aimed to analyze the risk factors for LPLN metastasis in patients with RNETs in order to guide surgical methods.MethodsWe searched relevant databases (PubMed, Embase, Medline, Cochrane Library, and Web of Science) for articles published between 1 January 2000 and 1 April 2024 to evaluate the risk factors for LPLN metastasis in patients with RNETs in this meta-analysis.ResultsA total of seven articles with 433 patients were included in this study. The overall results showed that a WHO grade > G1, tumor invasion of the muscularis propria or deeper, lymphovascular invasion (LVI), mesorectal lymph node metastasis (MLNM), and distant metastasis (M1) were significant risk factors for LPLN metastasis in patients with RNETs (P <0.05).ConclusionThis study identified key risk factors for LPLN metastasis in patients with RNETs, providing guidance for treatment strategies. A comprehensive evaluation of these risk factors and imaging findings is recommended to tailor personalized treatment strategies that optimize survival outcomes and improve quality of life.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024581891.